Strength assessment of historic brick masonry - Witzany, Jiří; Čejka, Tomáš; Sýkora, Miroslav; Holický, Milan (Journal of Civil Engineering and Management, 2016)
The identification of residual service life of a structure is an exceptionally demanding task in the case of reconstructed or newly modernised buildings. The identification of residual service life requires the study and knowledge of the mutual interaction of a building with its external environment, in particular, the time variable effects and impacts which lead to degradation processes and phenomena affecting and, in the absolute majority of cases, degrading the physical, mechanical and other properties of materials and structures. The article presents the results of in-situ and laboratory research of strength parameters of masonry from the start of the 20th century applying destructive and non-destructive tests. Besides, a probabilistic model and a procedure for the determination of masonry strength are described. It appears that the probabilistic approach leads to a design value by ca 5% higher than the deterministic approach. First published online: 08 Dec 2015